TESTING RETURN ON EQUITY AND RETURN ON ASSETS SIGNALS ON LQ45 ISSUERS - Hermawan, Hengki (RJABM (Research Journal of Accounting and Business Management), 2020)
This study aims to determine the effectiveness of the Return On Equity and Return On Assets signals at LQ45 issuers. M engujinya with multiple regression method on each object banks and manufacturing companies LQ45 companies subsequent visits magnitude of the effective contribution of Return on Equity and Return on Assets. The results of the research on the bank obtained that Return On Equity partially had no effect on stock prices and Return On Assets had an effect on stock prices, simultaneously Return on Equity and Return On Assets fell on stock prices, the Return On Assets signal was better than the Return On Equity signal. the results of research manufacturing companies Return On Assetspartially it does not have a significant effect on stock prices while Return On Equity partially has a significant effect on stock prices and simultaneously Return on Equity and Return On Assets have an effect on stock prices. While the signal is good Return On Equity leih of the signal Return On Assets. This study provides a new perspective on Return On Equity and Return On Assets in research.